The potential for Sour cherry orchard variety renewal in Ukraine - Shkinder-Barmina, Anna; Balian, Izolda; Шкіндер-Барміна, Анна Миколаївна; Балян, Ізольда Валеріївна (Dnipro : FOP Marenichenko V.V., 2025)
UA: The global production of sour cherry (Prunus cerasus L.) fruits amounts to approximately 1,1–1,3 million tons annually and reached 1,5 million tons in 2022, according to FAOSTAT data. Ukraine is among the key sour cherry-producing countries – together with Turkey, Poland, and others. In 2022, Ukrainian farms of all categories harvested about 180 thousand tons of fruits. The total area of sour cherry orchards worldwide is estimated at 225 thousand hectares, while in Ukraine (as of 2022) it covers about 20 thousand hectares. Analytical reports predicted that by 2024–2025, global production would remain stable or show a slight increase, approaching 1.6 million tons. However, in Ukraine, a reduction in orchard area has been observed, primarily due to complex socio-economic factors and the ongoing war. In Ukraine, sour cherry breeding has been carried out at the Institute of Horticulture of the National Academy of Agrarian Sciences of Ukraine (L.S. Reznichenko, N.V. Moiseichenko et al.); at the Melitopol Research Fruit Growing Station named after M.F.Sydorenko (S.P. Kedryn, M.T. Oratovskyi, M.I. Turovtsev, V.O. Turovtseva, A.M. Shkinder-Barmina); at the Bakhmut Research Station (L.I. Taranenko); and at the L.P. Symyrenko Research Station of Pomology (V.P. Laskavyi, V.V. Laskavyi).
Keywords: sour cherry (Prunus cerasus L.); sour cherry cultivars; breeding; orchard renewal; fruit production; productivity; disease resistance; winter hardiness; drought tolerance; Vidrodzhennia; Griot Melitopolskyi; Solidarnist; Ukraine